Gravettian Ceramic Firing Techniques in Central and Eastern Europe - Kuczyńska-Zonik, Aleksandra (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2014)
The main goal of this paper is to explore the diversity of Gravettian ceramics (30–20/16 thousand years ago), from Central and Eastern Europe. Most of the ceramic fragments were found in the Czech Republic. So far many ceramic analises have been made providing information about the technique of ceramic production in the Upper Paleolithic. Similar analyses have also been conducted in Russia allowing for comparing different types of ceramic production in various parts of Europe. The article discusses the finds ceramics from Czech (Pavlov, Dolni Věstonice) and Russian (Kostenki, Zaraysk) archaeogical sites and draws attention to features such as raw material, manufacturing and firing techniques and probable functions which such artefacts may have played. It is argued that the ability to produce ceramics in Gravettian cultures in Central and Eastern Europe developed at different times and in different ways.
Technologia wypalania ceramiki w kulturze graweckiej na terenie Europy Środkowej i Wschodniej
Keywords: Upper Paleolithic ceramics; ceramic production; ceramics from Central and East Europe